2015
DOI: 10.1007/s00382-015-2714-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impacts of cumulus, land surface and ocean surface schemes on summertime rainfall simulations over East-to-southeast Asia and the western north Pacific by RegCM4

Abstract: Examinations show that the combination of Emanuel, CLM and Zeng2 (E-C-Z2) yields the best overall results, consistent with the fact that physical mechanisms considered in E-C-Z2 tend to be more comprehensive in comparison with the others. Additionally, the rainfall quantity is found very sensitive to sea surface roughness length, and the reduction of the roughness length constant (from 2 × 10 −4 to 5 × 10 −5 m) in our modified BATS1e mitigates the drastic overestimation of latent heat flux and rainfall, and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
2
27
0
2
Order By: Relevance
“…The six experiments with Zeng1 show relatively better ranking scores compared to those with BATS1e and Zeng2 (Figure ). It is worth remembering that the default constant roughness length of 2 × 10 −4 m in BATS1e was overestimated when compared to the Zeng schemes, and the estimated values in Zeng1 were smaller than those in Zeng2 (Li et al , ). Among the three MIT‐Emanuel experiments, experiment 04 with the BATS1e ocean flux scheme gives the best result.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The six experiments with Zeng1 show relatively better ranking scores compared to those with BATS1e and Zeng2 (Figure ). It is worth remembering that the default constant roughness length of 2 × 10 −4 m in BATS1e was overestimated when compared to the Zeng schemes, and the estimated values in Zeng1 were smaller than those in Zeng2 (Li et al , ). Among the three MIT‐Emanuel experiments, experiment 04 with the BATS1e ocean flux scheme gives the best result.…”
Section: Resultsmentioning
confidence: 99%
“…Zeng1 and Zeng2), the values are estimated based on the friction velocity with Zeng2 taking into account the viscosity effect. Li et al () showed that the default value of roughness length in BATS1e was overestimated when compared to the Zeng schemes, while the estimated values in Zeng1 were smaller than those in Zeng2. A more detailed description of the 18 runs can also be found in Juneng et al ().…”
Section: Numerical Experiments and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng2 also take into account the effect of viscosity in the roughness length calculation. A detailed description of the effectiveness of these 3 air−sea flux schemes in RegCM4 has been reported by Li et al (2015). Table 1 summarizes the configurations for the 18 simulation experiments considered in our study.…”
Section: Model and Experimental Setupmentioning
confidence: 99%
“…The SS14 scheme does not consider the roughness sublayer effect and is valid for −5 ≤ Ri B ≤ 0, 10 ≤ z/z 0 ≤ 10 5 and 0 ≤ ln(z 0 /z 0h ) ≤ 29. As such, the SS14 scheme is not valid when z 0 becomes smaller than z 0h , which sometimes occurs over tall forests (e.g., Chen and Zhang 2009) and over oceans (e.g., Zeng et al 1998;Li et al 2015). …”
Section: Wrl12 Scheme and Ss14 Schemementioning
confidence: 98%